Rab1A promotes cell proliferation and migration by upregulating Gli1 in colorectal cancer - Chaozhong Peng (Nature Portfolio, 2021)
Abstract Rab1A, as a highly conserved small guanosine triphosphatase (GTPase), plays contentious roles in different types of cancers. The role of Rab1A in colorectal cancer (CRC) has been described in previous studies, but the molecular mechanisms of Rab1A in CRC remain far from being addressed. In the present study, we found that Rab1A expression was significantly upregulated in CRC tissues and increased Rab1A expression correlated with tumor size, lymph node metastasis (LNM) and tumor-node-metastasis (TNM) stage of CRC patients. We also found that Rab1A exerts its promotive effect on CRC cell proliferation, migration and EMT progress. Further mechanistic experiments showed that glioma-associated oncogene-1 (Gli1), as a key transcriptional factor of the Hedgehog pathway, was implicated in Rab1A-mediated regulation of CRC cell proliferation and migration. In addition, Rab1A upregulated Gli1 expression through Smoothened homolog (SMO)-independent pathway. Finally, Rab1A activated mechanistic target of rapamycin (mTOR) signaling in CRC cells. Collectively, our results define Rab1A as a novel regulator of Gli1 to promote CRC cell proliferation and migration, and suggest that the Rab1A/mTOR/Gli1 axis may serve as a promising therapeutic target for the treatment of CRC.